2002
DOI: 10.1002/1521-3862(20020116)8:1<21::aid-cvde21>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism Studies on Titanium Isopropoxide–Water Atomic Layer Deposition Process

Abstract: Reaction mechanisms between titanium isopropoxide and deuterated water in the atomic layer deposition (ALD) of TiO 2 at 150±350 C were studied using a quartz crystal microbalance (QCM) and a quadrupole mass spectrometer (QMS). The temperature had no marked effect on the total amount of the main gaseous by-product (CH 3 ) 2 CHOD. At 150±250 C, about half of the ligands were released in reactions with surface hydroxyl groups during the Ti(OCH(CH 3 ) 2 ) 4 pulse, and the other half during the water pulse. At high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
141
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 29 publications
14
141
1
1
Order By: Relevance
“…The transition from amorphous to anatase TiO 2 has been reported 180 C in the thermal ALD. 31 The mechanisms of the reaction between TTIP and water were studied by Rahtu and Ritala 37 and Aarik et al 31 using deuterated water to identify them. It was found that between 150 and 250 C half of the isopropoxide ligands are released during the TTIP pulse in reaction with hydroxyl groups and the other half are released during the water pulse.…”
Section: Water Processsupporting
confidence: 64%
See 1 more Smart Citation
“…The transition from amorphous to anatase TiO 2 has been reported 180 C in the thermal ALD. 31 The mechanisms of the reaction between TTIP and water were studied by Rahtu and Ritala 37 and Aarik et al 31 using deuterated water to identify them. It was found that between 150 and 250 C half of the isopropoxide ligands are released during the TTIP pulse in reaction with hydroxyl groups and the other half are released during the water pulse.…”
Section: Water Processsupporting
confidence: 64%
“…Xie et al 36 measured a growth rate of 0.03-0.15 Å /cycle between 50 and 150 C. They also reported an increase in the growth rate in the temperature range of 50-150 C, which does not agree with the results of this study. Both Rahtu and Ritala 37 and Ritala and Leskelii 38 reported a growth rate of 0.15 Å /cycle at substrate reported of 1.5 Å /cycle at the same substrate temperature. Sinha et al 40 also measured the growth rate at 160 C, which was 0.68 Å /cycle.…”
Section: Water Processmentioning
confidence: 99%
“…A first category directly monitors physical changes. Examples are quartz crystal microbalance [5][6][7][8] measuring mass change, four-point probe 9 measuring electronic resistivity, and thermopile 10 measuring the reaction enthalpies. A second category of techniques probes the gas species that are being consumed and formed during the various chemical reactions involved in the ALD process.…”
Section: Introductionmentioning
confidence: 93%
“…A second category of techniques probes the gas species that are being consumed and formed during the various chemical reactions involved in the ALD process. Examples are quadrupole mass spectrometry, 7,8,11 optical emission spectroscopy, 12,13 and Fourier transformed infrared (FTIR) absorption spectroscopy. 14 A last category uses light from either the infrared or visual range to monitor the optical properties of the surface and/or the deposited layer.…”
Section: Introductionmentioning
confidence: 99%
“…3 Its variability is generally explained by the dependence of the permittivity on the crystalline phase, deposition method and process parameters of the TiO 2 . Various techniques such as thermal 4 or anodic oxidation, 5 electron beam evaporation, 6 chemical vapor deposition (CVD), 7 plasma-enhanced chemical vapor deposition, 8 sol-gel methods, 9 reactive sputtering methods, 10,11 and atomic layer deposition (ALD) [12][13][14] have been reported for TiO 2 thin film fabrication. Among them, ALD seems highly suitable for obtaining conformal films with uniform thickness even at low temperatures, 15,16 allowing the manufacturing of insulator films with desired and reproducible properties.…”
Section: Introductionmentioning
confidence: 99%